MANAJEMEN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN PADA SMA INSHAFUDDIN BANDA ACEH - Raudhatul Juniati (FITRAH: International Islamic Education Journal, 2021)
The principal is a manager who is responsible for regulating educational activities in schools both academic and non-academic activities that have a strategic role in improving the quality of education. This study aims to determine the program, program implementation, program evaluation and the obstacles faced by school principals in improving the quality of education at SMA Inshafuddin Banda Aceh. This study uses a descriptive analysis method (Field Research) with a qualitative approach. Data collection techniques through observation, interviews, and documentation. The research subjects are principals and teachers. The results of the study show that: (1) School programs are prepared through deliberation, namely long-term programs every four years and short-term programs in one year and do not fully involve all personnel. The quality improvement program is documented in the annual program only and there is no preparation of semester programs and documentation objectives to be a reference for program implementation. (2) The implementation of the program begins with the division of tasks by forming an implementing committee team and each activity has a person in charge and the personnel in charge have never complained about resigning. (3) The evaluation is carried out by a committee team formed by the principal, namely the principal, deputy, senior teacher and supervisor, Providing instruments before conducting an evaluation and then analyzing and then making the next program in the following year, and (4) Obstacles faced by the principal In schools, some teachers do not understand in making lesson plans, teacher discipline is still lacking, students' interest in reading has decreased and infrastructure facilities are still inadequate.